First Nations Health Atlas: the evolution toward analyzing and reporting on First Nations wellness data in a good way - Waruk, Jillian; Taylor, Carole; Sinclair, Stephanie; Nickel, Nathan; Star, Leona (International Journal of Population Data Science, 2026)
The First Nations Health and Social Secretariat of Manitoba (FNHSSM) are leaders meeting the Truth and Reconciliation Commission of Canada’s Calls to Action to governments to generate annual reports on wellness of FNs in our region. FNs wellness publications typically contain data collected, validated, analyzed, and interpreted by non-FN people. FNHSSM advocates for data sovereignty for FNs to provide evidence for health advocacy, services funding, and rematriation of wellness practices to Nations. FNHSSM has a long-standing relationship with the Manitoba Centre for Health Policy at the University of Manitoba, which houses a large administrative data repository that includes decades of data spanning health care and wellness, education, social services, and justice. Large-scale reports, including the The Health Status of and Access to Healthcare by Registered First Nation Peoples in Manitoba (2019; “Health Atlas”), have been published through this partnership. Together, we are updating the Health Atlas. Because of the lack of FN representation in report generation, by engagement with FN Advisory, Community Members, Leadership, and Health Staff, this undertaking will be driven by FN methods and under the approval of the Health Information Research Governance Committee, guided by their 4 Principles of Respectful Research. The Atlas will rely on administrative datasets, but will incorporate the voices of FNs, FNs-led programming, and the inextricable value of culture, language, and spirit to wellness. It will be targeted for community use, published in smaller and more focused sections, include interactive, accessible dashboards, and be useful to the next generation of community-based FNs researchers.